STUDENTS’ LEARNING STRATEGIES IN VERBAL PRESENTATION IN THE FOURTH SEMESTER ENGLISH DEPARTMENT AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Eka Rahmawati; Nurdevi Bte Abdul; Hijrah (English Language Teaching Methodology, 2021)
This research aims to identify the learning strategies used by students in verbal presentation in the fourth semester English department at Muhammadiyah University of Makassar and to explain the way of verbal presentation strategy apply by students at Muhammadiyah University of Makassar. In this research, the researchers used descriptive qualitative design. The researcher did not used direct interview or face to face but the researcher conducted the interview via online. The result of this research showed that the students at Muhammadiyah University of Makassar used several learning strategies in verbal presentation, they are extempore strategy, memorandum strategy, and small note strategy but there is the most dominant strategy that used by student in verbal presentation, it is extempore strategy. In delivered their presentation there are several ways, 1). The speaker prepares the material with an outline only then during the presentation it will be explained in detail, 2). The student do not used the script in its delivery, the student only makes preparations by memorizing from the text where the contents are about the information to be conveyed, or 3). The student use note to write key word, several important note or key note. All of the learning strategies in verbal presentation that used by students can help students’ to make well their presentation in front of class.